Problems of Ex-Mining Land Reclamation Obligations in Positive Law in Indonesia - Mas Subagyo Eko Prasetyo (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to know: 1.How is the regulation of ex-mining land reclamation obligations under positive law in Indonesia? 2. What is the problem with setting the obligation for reclamation of ex-mining land in positive law in Indonesia?. The type of research carried out in this research is normative legal research, which is a scientific research procedure carried out to find the truth based on scientific logic from the normative side. Normative research is a process of finding laws, legal principles, and legal doctrines, in order to answer the legal issues faced. This normative legal research is carried out to produce new arguments, theories or concepts as prescriptions in solving problems at hand. The initial step carried out by research in the implementation of this normative research is to conduct research on the existing laws and regulations in Indonesia and the collection of materials is carried out through a literature study in the form of books, journals and so on to study the sources or written materials used can be used as material in writing this research. To answer the problem, the collection of legal materials is carried out by identifying and taking an inventory of the positive legal rules that apply in Indonesia, researching library materials such as books, scientific journals, and research reports, and other sources of legal materials relevant to the issues raised research will be conducted. The analysis of legal materials used in this research is to use a descriptive method, which is a method that focuses and focuses on problem solving, presentation, interpretation, and analysis so that it is expected to produce conclusions based on legal materials that can be accounted for.